Effectiveness of chlorine and peracetic acid in the disinfection of minimally processed cabbage (Brassica oleracea) and green plantain (Musa AAB) - Fatjó-Barboza, Esteban (2024)
Introduction. The consumption of minimally processed vegetables may pose health risks, making it imperative to understand the effectiveness of their disinfection. Objective. To evaluate the effect of peeling, cutting, and shredding on the effectiveness of sodium hypoclorite or chlorine (HClO) and peracetic acid (C2H4O3) in disinfecting cabbage (Brassica oleracea) and green plantain (Musa AAB). Materials and methods. The research was conducted at Centro Nacional de Ciencia y Tecnología de Alimentos, Costa Rica, in 2012. Cabbage and green plantain (unpeeled, peeled, cut, or shredded) were disinfected by immersion in chlorine solutions (200 mg l-1) and peracetic acid (80 mg l-1) to evaluate desinfectant concentration over time, the reduction of Escherichia coli in shredded samples, and their sensory characteristics. Results. Both disinfectants were stable in time except when the shredded vegetables were treated with the concentration decreasing faster for chlorine and shredded green plantain. In shredded cabbage, a greater reduction of E. coli (6,767 log10 UCF/g) was observed when peracetic acid was used compared to chlorine (4 log10 UCF/g), although both equal to the control (4 log10 UCF/g). In shredded plantain, reductions with chlorine (6 ± 1 log10 UCF/g) and peracetic acid (5,7 ± 0,7 log10 UCF/g) were different from those with water (3,17 ± 0,06 log10 UCF/g), but there were no significant differences between the two disinfectants. Sensory differences were detected for shredded cabbage disinfected with chlorine or peracetic acid, however, consumer acceptance must be assessed. Conclusions. The level of vegetable subdivision affected the effeciveness of chlorine and peracetic acid when disinfecting cabbage and green plantain. Peracetic acid provides greater reductions of E. coli than chlorine in the case of shredded cabbage and equivalent reductions in shredded green plantain.